Digital Transformation in Grocery Shopping: A Case Study of Segari Users in the Modern Market Era - Antonius Felix; Arihta Tarigan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Digital transformation has significantly reshaped grocery shopping behaviors, transitioning from traditional markets to digital platforms. This research explores how the adoption of e-commerce, specifically the Segari application, influences consumer purchasing patterns for staple groceries within the context of the modern market era. The primary issue addressed by this study is understanding the factors prompting consumers, particularly budget-conscious migrants, to shift their shopping habits from conventional to online marketplaces. Consequently, this research aims to identify critical elements influencing consumer preferences, purchasing behaviors, and satisfaction levels when using Segari. Employing a qualitative approach, this study integrates a comprehensive literature review and empirical data collected through structured interviews with selected respondents using the Critical Incident Technique (CIT). Respondents were budget-conscious migrants who regularly use Segari. Findings indicate that key factors driving consumer preference toward Segari include ease of access, broader product availability, promotional attractiveness, and stable pricing compared to traditional markets. Furthermore, consumers reported improved shopping convenience and higher satisfaction due to consistent pricing and efficient access to essential goods. This research offers valuable insights into consumer behavior shifts caused by digital adoption, providing strategic recommendations for e-commerce platforms like Segari to enhance user engagement and optimize customer satisfaction in a competitive market environment.